Designing Environment Care Adventure Game Based on Android Using Construct 2 - Ade Bastian; Yofi Awwaluddin; Whydiantoro; Budiman (Jurnal Mantik, 2021)
This lack of public concern for the environment makes education important for environmental education or environmental cleanliness, especially in early childhood, is very necessary as a personality formation and care for the environment, so that our environment and nature are always maintained. To provide education today, you must use media as a learning tool because currently technology has developed rapidly and considering that there are so many smartphone users that can be used and used as educational media tools. So that in this study an educational adventure game based on android has been developed with a short level, easy control and an increased level of difficulty. This game aims to provide education by picking up trash and sorting organic, inorganic, and hazardous waste properly. The method used in the development of this game is the Rational Unified Process (RUP), which includes several phases, namely Inception, Elaboration, Contruction, Transition. While the data collection method uses the method of observation, interviews, and literature study. The result of this research is an adventure game application that cares for the environment towards waste which is expected to be a medium of learning and education for the community, especially for early childhood so that they can find out how important it is to keep their environment clean and to preserve it and develop children's character who is sensitive to environmental cleanliness.